The Impact of Consumer Animosity on Purchase Unwillingness in a Boycott of Sari Roti - Usep Suhud (Bina Nusantara University, 2018)
This research was conducted in response to a boycott towards a national bread brand. It was stimulated by a company disclosure in stating they had no relation to any political events in 2016. This research aimed to examine the impact of consumer animosity on product judgment, purchase willingness, purchase unwillingness, and boycott participation. In total, 266 participants took part in this research using convenience sampling. Data were collected using an online survey. The data were analyzed using exploratory factor analysis and Structural Equation Model (SEM). This research finds that there is a significant impact of animosity on product judgment, purchase willingness, purchase unwillingness, and boycott participation. Moreover, there is also a significant impact of product judgment on purchase willingness and boycott participation on purchase unwillingness.